Cyathoshiva amaleshi gen. n. sp. n. (Nematoda: Cyatholaimidae) from the coast of India - Datta, Tridip Kumar; Miljutin, Dmitry M.; Chakraborty, Susanta Kumar; Mohapatra, Anil (Zootaxa, 2016)
A new genus, Cyathoshiva, of free-living marine nematodes from the subfamily Cyatholaiminae (family Cyatholaimidae, order Chromadorida), is described from the Indian coast. The new genus differs from other known Cyatholaiminae genera in having a unique combination of morphological characters: buccal cavity with well-developed dorsal tooth and two subventral teeth, proximally unpaired gubernaculum and non-cup shaped supplements. The type species Cyathoshiva amaleshi gen. n. sp. n. is characterized by having multispiral amphids with 4.5 turns, punctated cuticle with a weak lateral differentiation, a conical tail, three supplements possessing both tubular and setoid parts, and a gubernaculum with a serrated and dentate distal end.